Analisis Yuridis Penggunaan Earphone di Area Kerja PT X Berdasarkan Permenaker Nomor 5 Tahun 2018 tentang Keselamatan dan Kesehatan Kerja Lingkungan Kerja - reynaldy ryan permana; Muhamad Abas, S.H.,M.H; Dr. Yuniar Rahmatiar, S.H.,M.H (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the risks of earphone use in industrial work areas from the perspective of Occupational Safety and Health (OSH) based on the Indonesian Minister of Manpower Regulation Number 5 of 2018. The use of earphones while working may reduce concentration, hinder communication and decrease workers’ ability to hear warning signals. This research employed an empirical juridical method through observations and interviews with relevant stakeholders. The findings indicate that risk control is implemented through company policies, socialization, supervision, training and disciplinary measures. Earphone use also causes a masking effect that may delay workers’ responses to hazards. Therefore, restricting earphone use in high-risk work areas is essential to enhance worker safety and protection. Implementing these control measures requires the support of employee awareness and company commitment to foster a safe working environment in accordance with occupational health and safety principles.